Formulation, Characterisation, and Biocompatibility Assessment of Rifampicin-Loaded Poly(d,l-lactide-co-glycolide) Composites for Local Treatment of Orthopaedic and Wound Infections - Mitali Singhal; Colin C. Seaton; Alexander Surtees; Maria G. Katsikogianni (MDPI AG, 2024)
Background/Objectives: The escalating challenge of antimicrobial resistance (AMR) necessitates the development of targeted antibiotic delivery platforms, minimising systemic administration. Polymer-based drug delivery emerges as a promising solution, ensuring sustained release and prolonged efficacy of bioactive compounds, ensuring long-term efficacy. Methods: This study focuses on encapsulating rifampicin (RIF), a key antibiotic for orthopaedic and wound-related infections, within Poly(d,l-lactide-co-glycolide) (PLGA), a biodegradable polymer, through solvent casting, to formulate a PLGA-RIF composite membrane. Comprehensive characterisation, employing Fourier-transformed infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), thermal analysis and X-ray Diffraction (XRD), confirmed the integrity of both the starting and produced materials. UV-Vis spectroscopy revealed a controlled drug release profile over 21 days in various media, with the chosen media influencing the drug release, notably the tryptic soya broth (TSB) caused the highest release. The quantitative assessment of the antimicrobial efficacy of the developed PLGA-RIF composite was conducted by measuring the size of the inhibition zones against both Gram-negative and Gram-positive bacteria. Results: The results confirmed the composite's potential as a robust antibacterial biomaterial, demonstrating a rapid and effective antibacterial response. Cytocompatibility tests incorporated human fibroblast and osteoblast-like cell lines and demonstrated that the RIF:PLGA (1:8) formulation maintained eukaryotic cell viability, indicating the composite's potential for targeted medical applications in combating bacterial infections with minimal systemic impact. Conclusions: This study presents the significance of investigating drug release within appropriate and relevant physiological media. A key novelty of this work therefore lies in the exploration of drug release dynamics across different media, allowing for a comprehensive understanding of how varying physiological conditions may influence drug release and its effect on biological responses.